From Bastuhara to Immigrati: Resistance and Refugee Solidarity in Amitav Ghosh’s The Hungry Tide and Gun Island - De, Asis; Misra, Maitrayee (The Outlook: Journal of English Studies, 2023)
Refugees exist throughout human history, though it is after the British imperial collapse that the term ‘refugee’ finds currency in South Asia. This paper shows how refugee solidarity finds different expressions in the face of resistance and securitization in two of Amitav Ghosh’s novels ˗ from the state-sponsored genocide of refugees in the regime of a left-wing government in The Hungry Tide, to the right-wing resistance denying the entry of immigrants stranded on the Italian coastline of the Mediterranean in Gun Island. This paper also unfolds how politicization of issues like sheltering and socializing the refugees affects the idea of solidarity: the indifference of civic society to state-sponsored atrocities against the refugees in The Hungry Tide stands in contrast with the support extended to illegal immigrants by the human rights activists despite the opposition of “right-wing, anti-immigrant groups” in Gun Island. Finally, the paper reflects how, in this age of economic globalization, digital media appears more powerful than any doctrinaire ideology of the ‘dispossessed’ in managing refugees’ solidarity.